Black males and intercollegiate athletics : an exploration of problems and solutions - Bennett, Robert A. III; Hodge, Samuel R.; Graham, David L.; Moore, James L., III (Diversity in higher education, 2015)
This volume focuses on the issues African American males face not only as participants in athletic competition as student-athletes but also as coaches, administrators, and academic support staff. It will serve as a valuable resource for educational policy makers, especially athletic association personnel (i.e. NCAA), and other constituents.